Characterization of the KATRIN cryogenic pumping section. (February 2023) - Röttele, C.; Steidl, M.; Sturm, M.; Röllig, M.; Marsteller, A.; Schimpf, L.; Friedel, F.; Jansen, A.; Gil, W.; Schrank, M.; Wolf, J.; Drexlin, G.; et al.
Abstract: The KArlsruhe TRItium Neutrino (KATRIN) experiment aims to determine the effective anti-electron neutrino mass with a sensitivity of 0.2 eV/c 2 by using the kinematics of tritium β -decay. It is crucial to have a high signal rate which is achieved by a windowless gaseous tritium source producing 10 11 β -electrons per second. These are guided adiabatically to the spectrometer section where their energy is analyzed. In order to maintain a low background rate below 0.01 cps, one essential criteria is to permanently reduce the flow of neutral tritium molecules between the source and the spectrometer section by at least 14 orders of magnitude. A differential pumping section downstream from the source reduces the tritium flow by seven orders of magnitude, while at least another factor of 10 7 is achieved by the cryogenic pumping section where tritium molecules are adsorbed on an approximately 3 K cold argon frost layer. In this paper, the results of the cryogenic pumping section commissioning measurements using deuterium are discussed. The cryogenic pumping section surpasses the requirement for the flow reduction of 10 7 by more than one order of magnitude. These results verify the predictions of previously published simulations. Highlights: Measurement of the reduction factor of KATRIN's cryogenic pumping section with deuterium. Safe tritium retention can be concluded. More than 10 8 gas flow reduction.